Peer moderation of asynchronous online discussions: an exploratory study of peer e-moderating behaviour - Ghadirian, Hajar; Mohd Ayub, Ahmad Fauzi (Australasian Society for Computers in Learning in Tertiary Education, 2017)
This study explored patterns of e-moderating behaviour students performed when they were assigned as peer moderators of asynchronous online discussions in a reciprocal manner. Eighty-four students from an undergraduate blended course were observed during a 7-week-long online discussions. Using quantitative content analysis peer moderators’ interventions were analysed based on Smet, Keer, Wever, and Valcke’s (2010) scheme. The descriptive results show information exchange and knowledge construction supports were of continuous importance. Finally, a cluster analysis identified three distinct patterns of e-moderating behaviour: low-level moderators, mid-level moderators, and high-level moderators. The clusters differed in types of e-moderating support as well as their patterns of participation. High-level moderators dominated knowledge construction support and showed high level of online participation. Mid-level moderators dominated information exchange support and exhibited a moderate level of participation. Socialisation support and low level of participation were characteristics of low-level moderators. We further examined how these approaches were related to peer moderators’ perceptions of online discussions and academic performance. The results indicate that high-level moderators scored highest on all aspects of perceptions of online discussions and outperformed peer moderators in the other clusters with regard to academic performance.